Forming technological traits of dry milk - Radaeva, I. A.; Kruchinin, A. G.; Turovskaya, S. N.; Illarionova, E. E.; Bigaeva, A. V. (Vestnik MGTU, 2020)
Dry milk is used in a wide variety of products due to its high energy value and long shelf life. Its use is especially valuable in the dairy industry, since it smooths the seasonality of raw milk production. Moreover, dry milk makes it possible to generate socially essential products in the regions of Russia where dairy farming is not developed or where it is impossible to produce raw milk. There are different methods to form dry milk's traits and the required functional features like cheesability, heat stability and solubility. Among these methods we emphasize on technological ones, based on prevention measures of impact on raw milk during its processing. As a result, methods for the increase of dry milk's heat stability are among the most essential, since its low values make it impossible to generate products of high quality or to use this milk in any processing at all. A number of foreign and national works are dedicated to the improvement of dry milk's heat stability. These studies offer various methods like an effective refining of raw milk, its preliminary heat treatment, the use of specific food supplements and raw milk components, the correction of physicochemical values, the variation of temperature regimes, the use of unconventional equipment for desiccation and condensation. Integrated methods of heat stability increase do not require core changes in the current technological requirements of dry milk production and can be integrated into the existing production conditions, thus they arose a lot interest and have prospects. This overview allows to broaden knowledge and to find new methods to form technological traits of not only dry milk, but canned milk as well.